(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Theileriosis is one of the blood-parasitic diseases of cattle and is considered the most dangerous among them. This disease occurs in all regions of our country and causes great economic damage to livestock. High mortality of animals from the disease (40-80%), i.e. abortions, reduced birth and milk yield, decreased weight and quality of meat of slaughtered animals, and costs of keeping and treating sick animals are determined.